Profil Hemosit dan Aktifitas Fagositosis Kepiting Bakau (Scylla sp.) yang Terserang Ektoparasit di Ekosistem Mangrove Kuta Selatan, Bali - Alfi Hermawati Waskita Sari; Rani Ekawaty (Fakultas Kelautan dan Perikanan Universitas Udayana, 2016)
Mangrove crab (Scylla sp.) is one of the commodities that live in the mangrove ecosystem and were developed through cultivation, but it encountered many obstacles in its development mainly due to parasitic infection. The purpose of this study is to determine the hemocytes profile and the phagocytic activity of the mud crab (Scylla sp.), in terms of parasitic infection and the water quality of the mangrove ecosystem in South Kuta, Bali. The results of study showed the Haemocyte Total Count (THC) of mangrove crab in the range of 1.8 to 2.57x106 cells/ml and Haemocyte Differential Count (DHC) mud crab shows the percentage of cells hyalinosit 14-32%, 24-38% and the semigranulocytes cells 39-58% of granulocytes cells, phagocytosis percentage of the mud crab (Scylla sp.) are in the range of 53%-66%, while the index of phagocytosis 1.81-2.11. Type ectoparasites found in mangrove crab (Scylla sp.), among others are Vorticella sp., Zoothamnium sp. and Epistylis sp.